Penilaian Kompetensi Mengaji Calon Guru Melalui Teknik Analisis Matrik USG di SDIT Baitul Izzah Nganjuk - Saputra, Bagus Rachmad (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2020)
This study aims to help schools namely SDIT Baitul Izzah (Baiz) Nganjuk Regency to solve human resource problems by using USG matrix analysis techniques. This research uses a qualitative research approach by conducting field studies directly observing the field, interviewing the principal as a resource person, and conducting documentation studies relating to the recruitment process of new teachers. The results of this study found: (1) the problem of human resources in schools about the prospective teachers recruited lacking the ability to study, (2) USG matrix analysis techniques used to analyze human resource problems in schools, (3) suggestions and solutions to schools to solve the problem of human resources about prospective teachers recruited lacking the competence to read through the results of problem analysis using USG matrix techniques.